Implementation of CMOS oscillator for CMOS SAW resonator - Karim, Jamilah; Nordin, Anis Nurashikin (IEEE, 2016)
This work presents a design and measurement of pierce oscillator circuit for microelectromechanical system (MEMS) SAW resonator. The pierce oscillator circuit was fabricated using MIMOS 0.35um CMOS technology process. The pierce oscillator circuit provides gain to offset the losses of the resonator. The open loop gain of the fabricated oscillator circuit is 17.5dB and consumes 3mW power. When integrated with SAW resonators, the phase noise performance is -84.6dBc/Hz 100 kHz offset frequency. The far from carrier noise is -103dBc/Hz.